How to increase rural NEETs professional involvement in agriculture? The roles of youth representations and vocational training packages improvement - Simões, F.; Rio, N. B. (Journal of Rural Studies, 2020)
Our general aim is to explore how training experiences in agriculture can be tailored to improve the prospects of low-qualified, rural youths who are neither in employment, nor in education or training (NEET) being involved in the sector. We conducted two sequential qualitative studies in The Azores Islands, a remote and mostly rural Portuguese region, using a Participatory Action Research (PAR) approach. Study 1 involved 16 youths aged 18–23 years old (M age = 20.51; SD = 1.75; eight female) and consisted of four focus group discussions, which underwent a content analysis. Study 2 consisted of three world-café sessions with, respectively, five youths, seven representatives of private and public stakeholders and six representatives of the agriculture sector. Study 1 showed that low-quali- fied rural NEETs depict negative perceptions about agriculture. These negative perceptions are similar, in content, to those reported in other studies by youths originating in (sub)urban areas. Study 2 highlighted that a strong participatory stand to design and run training for agriculture has the potential to tailor packages that improve outreaching these youths. Furthermore, it prevents their negative representations and tackles the mismatch be- tween training offer and local economy opportunities. These conclusions are relevant across Southern European countries, which are struggling with higher numbers of rural NEETs, as well as with weak institutional support to uphold the transition from school to work.